Ethanol Selectively Attenuates NMDAR-Mediated Synaptic Transmission in the Prefrontal Cortex - Weitlauf, Carl (2008)
BACKGROUND: Brain imaging studies have revealed abnormal function in the prefrontal cortex (PFC) of alcoholics that may contribute to the impulsive behavior and lack of control over drinking that characterizes this disorder. Understanding how ethanol affects the physiology of PFC neurons may help explain this loss of control and lead to better treatments for alcohol addiction. In a previous study from this laboratory, we showed that ethanol inhibits complex patterns of persistent activity (known as “up-states”) in medial PFC (mPFC) neurons in a reversible and concentration-dependent manner. METHODS: In the current study, whole-cell patch clamp recordings were used to directly examine the effects of ethanol on the glutamatergic and GABAergic components that underlie persistent activity. RESULTS: In deep-layer mPFC pyramidal neurons, ethanol reversibly attenuated electrically evoked N-methyl-d-aspartate-type glutamate receptor (NMDAR)-mediated EPSCs. Significant inhibition was observed at concentrations as low as 22 mM, equivalent to a blood ethanol concentration (0.1%) typically associated with legal limits for intoxication. In contrast to NMDA responses, neither evoked nor spontaneous EPSCs mediated by α-amino-3-hydroxy-5-methylisoxazole-4-propionic acid-type glutamate receptor were affected by ethanol at concentrations as high as 88 mM, a concentration that can be fatal to non-tolerant individuals. At similar concentrations, ethanol also had little effect on spontaneous or evoked IPSCs mediated by a-type γ-amino-butyric acid receptor. Finally, mPFC neurons showed little evidence of GABAR-mediated tonic current and this was unaffected by ethanol. CONCLUSIONS: Together, these results suggest that NMDAR-mediated processes in the mPFC may be particularly susceptible to disruption following the acute ingestion of ethanol.